Pros and cons : INSIDE O.K.U stop center in UiTM / Muhammad Reza Ahmad - Ahmad, Muhammad Reza (2013)
Over the last 20 years, there is no topic that causes more controversy in special education among teachers, administrators, and parents than INSIDE Stop center Inclusion represents the belief of philosophy that the students with disabilities should be integrated into the regular education classrooms whether or not they can meet traditional curricular standards especially in UiTM. The purpose of this study was to examine the potential pros and cons of the INSIDE Stop center of students with disabilities into regular education classrooms in UiTM. This study included a comprehensive review and critical analysis of research and literature concerning the issue of inclusion and INSIDE Stop center, the factors that contributed to the movement to educate students in INSIDE Stop center classrooms, inclusion versus mainstreaming, what the least restrictive environment is, models of inclusion, what an INSIDE Stop center classroom looks like, and the pros and cons for special education students, regular education students, and regular education teachers when placing students with disabilities into regular education classrooms in UiTM. Research has shown that INSIDE Stop center promotes the idea that students with disabilities should begin in the regular education classroom, and be removed only when appropriate services cannot be provided there. When implemented properly, inclusion can have many pros for all students and teachers involved in the process